PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA BIRO UMUM PROVINSI SULAWESI SELATAN - Ananda Suryadarman, Andi Ayu; Rifdan; H, Herman; Andi Anugrah Mahyuddin (International Journal Of Public Policy and Bureaucracy, 2024)
This study examines the impact of transformational leadership style and work motivation on employee performance within the General Bureau of South Sulawesi Province. Employing a quantitative research method, data was collected through a structured questionnaire distributed to 113 respondents. The analysis was conducted using Structural Equation Modeling (SEM) to evaluate the relationships between variables. The findings indicate that transformational leadership significantly influences employee performance by creating an environment that fosters innovation, collaboration, and goal alignment. Leaders who demonstrate a clear vision, inspire their teams, and attend to individual needs positively affect the productivity and efficiency of employees. Similarly, work motivation is shown to have a strong and positive effect on employee performance. Motivational factors, including recognition, opportunities for professional growth, and a supportive work environment, encourage employees to excel in their roles and achieve organizational goals. The results further suggest that when both transformational leadership and work motivation are combined, their impact on employee performance becomes even more significant, highlighting the importance of a balanced approach in leadership and motivation. This research highlights the critical role of leadership and motivation in public administration, especially in enhancing the overall performance of government institutions. The study suggests that investing in leadership development programs and motivational strategies can lead to improved employee outcomes and organizational effectiveness. Recommendations for policymakers and managers include providing regular training for leaders, fostering open communication channels, and implementing reward systems tailored to employees' needs. Furthermore, this study contributes to the existing literature by emphasizing the synergistic effects of transformational leadership and work motivation in a public sector context, particularly in Indonesia. By addressing these factors, organizations can adapt to the dynamic demands of public administration and deliver better services to the community. Future research could explore other variables, such as organizational culture or job satisfaction, to provide a more comprehensive understanding of the determinants of employee performance.